Therapeutic Aspect OF Derived Position FOR Stroke Patients - J, Gokulakrishnan; M, Thameem Ansari; M, Naveenkumar; P, Sharukesh (International Journal of Allied Medical Sciences and Clinical Research, 2025)
Stroke remains a major cause of long-term disability, leading to impairments in motor function, muscle tone, and postural control. Positioning strategies play a vital role in stroke rehabilitation, as incorrect posture may contribute to contractures, spasticity, and pressure sores. Derived positions—specific postural modifications based on biomechanical and neurophysiological principles—are used to optimize muscle activity and facilitate recovery.